Politik Hukum Pembentukan Peraturan Perundang-Undangan Pasca Perubahan Kedua Undang-Undang Nomor 12 Tahun 2011 - Febriani, Nadia Ayu; Wasti, Ryan Muthiara (Universitas Serang Raya, 2023)
Article 22A of the 1945 Constitution of the Republic of Indonesia mandates the establishment of a rule regarding the law-making process, which serves as a guideline for the law-making process from its inception until the regulation is enacted to the public. However, in its implementation, problems are still related to the law-making process in Indonesia. This normative research uses a statutory and conceptual approach that specifically looks at